Research on the stock volatility of listed banks in China - Fuyuan, Lu (2022)
The Chinese stock market has achieved many successes, but there are also many problems that make the Chinese stock market far more volatile than mature stock markets in developed countries. It is therefore essential for the Chinese financial sector to study the dynamic volatility characteristics of the stock market and to implement risk management. Moreover, commercial banks are at the core of a country’s economy, so fluctuations in their stock yields have a significant impact not only on the banking sector but also on the whole stock market. Based on these two reasons, this paper selects the commercial banking sector to explore the characteristics of share price volatility, which is important for the empirical study in the Chinese stock market. The purpose of this paper is to examine the return and volatility characteristics of Chinese commercial bank stocks, such as the presence of ARCH effects, aggregation effects and leverage effects. The sample is selected from state-owned and joint-stock commercial banks and ARIMA-GARCH, GARCH-M and TGARCH models were constructed. Our main finding from the model is that the distribution of commercial bank stock returns is leptokurtic and fat-tailed. Secondly, the volatility of commercial banks is positive during the statistical period, but investors can gain the corresponding return from the risk. Finally, past volatility in stocks does not disappear immediately, but has a persistent effect on stocks.